Prison System Transformation: Delving into Restorative Justice, Rehabilitation, and Religious Life Based on Islamic Law - Karimullah, Suud Sarim (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2023)
This study explores the idea of the transformation of prison systems based on Islamic law to understand the contribution of Islamic principles and practices to the effectiveness and fairness of the prison system as a whole. The research method involves a systematic and comprehensive literature review to understand the conceptualization of Islamic law in the context of the prison system and previous studies. It aims to establish a strong theoretical basis, identify research gaps, explore existing empirical evidence, and make a significant contribution to understanding Islamic law's application in the prison system. The results of this study conclude that integrating Islamic law into the prison system can make an important contribution to rehabilitating prisoners, promoting restorative justice, and providing fair and equal religious accommodation. However, its implementation must be carried out carefully, considering the principles of justice, human rights, and religious diversity. Collaboration and dialogue between prison institutions, scholars, and related parties are also needed to strengthen comprehensive understanding, overcome misconceptions, and ensure that implementing Islamic law in the prison system is carried out properly and in line with human rights principles.